Evaluation the Program of KOTAKU (City Without Slums) (Study at Mariso Districts, Mariso Village, Makassar City) - Mega Utami Putri; Muhammad Nur Yamin (Pinisi Journal of Social Science, 2022)
This study aims to determine the evaluation of the implementation of the City Without Slums Program (KOTAKU) at Mariso Districts, Mariso Village, Makassar City, and the impact of the implementation of the Slumless City Program (KOTAKU) at Mariso Districts, Mariso Village, Makassar City. This study uses a qualitative research type with a descriptive approach. Data collection techniques were carried out by observation, interviews, and documentation. The data analysis technique in this study used the analysis model according to Spradley. The results of this study indicate that the implementation of the KOTAKU (City Without Slums) Program Evaluation (Study at Mariso Districts, Mariso Village, Makassar City) is not implemented well in accordance with the concept of Edward a Suchman. Indicators that do not work well are: a. program objectives, b. problem analysis, c. measurement of change, d. changes to the consequences of activities, e. program impact. The indicators that run well are description and standardization. The impact of the City Without Slums Program (KOTAKU) is that not all people can feel the infrastructure development in Mariso Village. The lack of community participation in maintaining infrastructure has mede the City Without Slums (KOTAKU) Program less successfull.